Environmental variability of the last 1600 years derived from a multiproxy lake record of the east Andean margin (46.7°S), central west Patagonia, Chile - Franco, C. (2025)
Central west Patagonia is directly exposed to influence of the Southern Westerly Winds (SWW). Its position relative to the core of this major wind system makes this region highly susceptible to magnitude and latitudinal changes of the SWW. Moreover, the pronounced topography defines a strong west-east moisture gradient. We present an environmental reconstruction derived from sediments of Laguna Vogt, a lake located in one of the easternmost valleys of central west Patagonia. Our reconstruction shows that increased runoff triggered the remobilization of basaltic material, while lacustrine production remained low between 1600-1300 and 1000-750 cal yr BP. Between 1300-1000 and 750-250 cal yr BP, these conditions changed to decreased surface runoff, with less clastic input favoring high autochthonous sedimentation, while several episodes of flooding occurred. Our findings indicate that intervals of enhanced runoff at Laguna Vogt correlate with a regional period of increased precipitation, which started to decline around 800 cal yr BP. Climate reconstructions suggest that increased precipitation was a direct result of intensified SWW. Thus, periods of high lacustrine productivity interspersed with episodes of intense flooding are interpreted as shifts between wet-cold and dry-warm conditions occurring on decadal to multidecadal timescales. Around 250 cal yr BP, fluvial detrital input into the lake became dominant, suggesting the establishment of wetter conditions. This increase in precipitation, also documented by other sediment records from central west Patagonia, is associated with intensified SWW. Such a timing compares well with multiple regional glacial advances, indicating an environmental shift likely associated to the last glacial stage of the Holocene.